Health-Seeking Behaviors and Self-Care Practices of People with Filarial Lymphoedema in Nepal: A Qualitative Study - Ram Kumar Adhikari; Jeevan Bahadur Sherchand; Shiva Raj Mishra; Kamal Ranabhat; Amrit Pokharel; Pramila Devkota; Durga Mishra; Yadu Chandra Ghimire; Khageshwor Gelal; Rajan Paudel; Rajendra Raj Wagle (Journal of Tropical Medicine)
Background. Lymphatic filariasis is endemic in Nepal. This study aimed to investigate health-seeking behaviors and self-care practices of people with filarial Lymphoedema in Nepal. Methods. A cross-sectional study was conducted using qualitative methods in three endemic districts. Twenty-three patients with current Lymphoedema were recruited in the study. Results. Hydrocele was found to be a well-known condition and a major health problem in the studied communities. People with Lymphoedema primarily sought health care from traditional healers, whereas sometimes home-based care was their first treatment. Later Ayurvedic and allopathic hospital-based care were sought. Respondents reported various psychological problems such as difficulty in engaging in sexual intercourse, anxiety, worry and stress, depression, low self-esteem, feeling weak, fear of being abandoned, and fear of transmitting disease to the children. Standard foot care practices except washing were largely absent. Conclusions. Lymphoedema in the limbs and hydrocele were found to be major health problems. The traditional health care providers were the first contact of care for the majority of respondents. Only a few patients had been practicing standard foot care practices.